Tanimilast, A Novel Inhaled Pde4 Inhibitor for the Treatment of Asthma and Chronic Obstructive Pulmonary Disease - Fabrizio Facchinetti; Maurizio Civelli; Dave Singh; Alberto Papi; Aida Emirova; Mirco Govoni (Frontiers Media S.A., 2021)
Chronic respiratory diseases are the third leading cause of death, behind cardiovascular diseases and cancer, affecting approximately 550 million of people all over the world. Most of the chronic respiratory diseases are attributable to asthma and chronic obstructive pulmonary disease (COPD) with this latter being the major cause of deaths. Despite differences in etiology and symptoms, a common feature of asthma and COPD is an underlying degree of airways inflammation. The nature and severity of this inflammation might differ between and within different respiratory conditions and pharmacological anti-inflammatory treatments are unlikely to be effective in all patients. A precision medicine approach is needed to selectively target patients to increase the chance of therapeutic success. Inhibitors of the phosphodiesterase 4 (PDE4) enzyme like the oral PDE4 inhibitor roflumilast have shown a potential to reduce inflammatory-mediated processes and the frequency of exacerbations in certain groups of COPD patients with a chronic bronchitis phenotype. However, roflumilast use is dampened by class related side effects as nausea, diarrhea, weight loss and abdominal pain, resulting in both substantial treatment discontinuation in clinical practice and withdrawal from clinical trials. This has prompted the search for PDE4 inhibitors to be given by inhalation to reduce the systemic exposure (and thus optimize the systemic safety) and maximize the therapeutic effect in the lung. Tanimilast (international non-proprietary name of CHF6001) is a novel highly potent and selective inhaled PDE4 inhibitor with proven anti-inflammatory properties in various inflammatory cells, including leukocytes derived from asthma and COPD patients, as well as in experimental rodent models of pulmonary inflammation. Inhaled tanimilast has reached phase III clinical development by showing promising pharmacodynamic results associated with a good tolerability and safety profile, with no evidence of PDE4 inhibitors class-related side effects. In this review we will discuss the main outcomes of preclinical and clinical studies conducted during tanimilast development, with particular emphasis on the characterization of the pharmacodynamic profile that led to the identification of target populations with increased therapeutic potential in inflammatory respiratory diseases.